Temporal Artery Biopsy Debate: Positive TAB Result Prolongs Steroid Use in Giant Cell Arteritis. Issue 11 (22nd November 2022) - Ponich, Brett; Lafreniere, Ann-Sophie; Hartley, Rebecca; Temple-Oberle, Claire F.
Abstract : Background: Temporal artery biopsy (TAB) in diagnosing giant cell arteritis has been criticized due to surgical risks, a high false negative rate, and redundant information when patients already met American College of Rheumatology criteria. The objective of this study was to investigate TAB's impact on steroid treatment duration. Methods: A retrospective chart review garnered patient demographics, symptoms, comorbidities, and steroid treatment duration in patients undergoing TAB at a single center. Steroid treatment was compared between TAB+ and TAB - patients. Results: One hundred seven patients undergoing TAB were included. Patients were predominantly women (70.1%) with a median age of 74 years (46 -91). Of 107 TAB results, 74 (69.2%) were negative, 23 (21.5%) were positive, and 10 (9.3%) were found to be indeterminate. In TAB+ patients, the mean erythrocyte sedimentation rate was not significantly different than TAB - patients (60.2 versus 43.7, P = 0.45), nor was the median C-reactive protein (38.8 versus 18.1, P = 0.17). Regarding steroid use, both TAB+ and TAB - patients had a similarly high rate of prebiopsy steroid initiation (82.6% versus 70.3%, P = 0.32). More TAB+ patients remained on steroids at 6 weeks (95.0% versus 57.4%, P = 0.004), 6 months (95% versus 37.7%, P < 0.001), 1 year (65.0% versus 31.1%, P = 0.024), and 18 months (50.0% versus 19.7%, P = 0.045). By 2 years, the difference no longer met significance (35.0% versus 14.8%, P = 0.12). P = 0.12). Conclusion: TAB positivity does seem to influence maintenance of steroids up to 18 months after biopsy.